PERAN KONSEP DIRI DAN DUKUNGAN SOSIAL PADA KECEMASAN BERBICARA DI MUKA UMUM - Imam Sunardi (Psympathic : Jurnal Ilmiah Psikologi, 2010)
The objective of this research was to study the role of self concept and social support on public speaking anxiety of dakwah faculty students. Fifty one students of dakwah faculty of Sunan Gunung Djati Islamic Religion National Institute Bandung participated in this study. All of subjects studied at grade VII at the Islamic Counseling Program and Islamic Community Development Program. They were given three kinds of scales: public speaking anxiety scale, self concept scale, and social support scale. The results of regression analysis showed that self concept played a role on public speaking anxiety (rPartial = -0,435; t = -3,343; p = 0,002) and the contribution was about 19,803 percent. Social support had no significant role on public speaking anxiety (rPartial = 0,117; t = 0,814; p = 0,575), and the contribution was about 2,013 percent only. Self concept had several aspects that were physical self, moral-ethic self, personal self, family self, and social self. One of those aspect, that was personal self, play a role on public speaking anxiety significantly (rPartial = -0,369; t = -2,667; p = 0,010). Another result showed that no aspect of social support has role on public speaking anxiety significantly.